EJA: saberes na articulação curricular da Escola Municipal Professor Amadeu Araújo - Santos, Veridiano Maia do (2014)
The target of this paper is to investigate the possibilities of inscribing into the EJA curriculum the knowledge detected in the neighborhood of a school if the point of view of the student body regarding the basic schooling deserves its due consideration. The empirical field of our research focuses on the elementary school of professor Amadeu Araújo Municipal School in Natal. Our investigative course tried to understand the way pupils think the curriculum contents of knowledge spread around the school from the vision furnished by their elementary school. With this, we hoped to develop a creative understanding concerning that question. Then we reviewed, along the debate, questions related to Nova Natal Housing Estate and its historic, social and cultural beginnings taking in account the participants memories of this research and their suggestions concerning the utility of the community knowledge to the curriculum practices. This project is supplied by the qualitative research and reinforced by the Focal Group s methodological procedures and semi-structured interviews. This procedure allowed us to discern different points of viewing, feeling and understanding in the complexity of the daily life around school and its environment. With these elements, we could note that some students perceptions pointed to a basic schooling fomented by traditionalized pedagogical practices in which teacher and pupil seldom dialogue with each other, what corroborates the impression of undervaluation of the pupil s role. Consequently, the nets of knowledge waved around the school in Nova Natal Housing Estate become useless, when they could be of great utility if inserted in the curriculum contents